The Role of Predictive Analytics in Knowing the Future Prices of Listed Stocks in The Market - Alanazi, Reem Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to identify the role of predictive analytics in knowing future stock prices listed in the market, where the researcher used the descriptive analytical method, and the study sample amounted to (13) of industrial companies listed on the stock exchange.The study came out with resultsThe financial ratios derived from the income and financial position statements play an effective role in distinguishing between successful companies and failed companies.The proposed model based on the financial ratios derived from the income and financial position statements was able to reclassify the sample of companies used in its design within the groups (successful companies) and (failed companies).The proposed model based on the financial ratios derived from the income and position statements was able to predict financial failure in the sample of companies used in testing it within the groups (successful companies) and (failed companies).With regard to the relationship between the dependent variable and the independent variable, there is a statistically significant effect on the dependent variable. In other words, an increase in the debt ratio leads to an increase in the value of the company.With regard to the relationship between the dependent variable and the independent variable, the policy of distributions has indicated that there is no statistically significant effect on the dependent variable.Activating the use of debt by companies that use a low debt ratio through profitability, as the more profitable companies can use more debt and thus reduce the risk of debt.The impact on the distributions policy so that it is related to the degree of greater benefit from the funds between distribution and retention, as the higher dividends on the returns of alternative investment opportunities than investing in companies leads to an increase in the value of the company.Increasing profitability rates by increasing efficiency by reducing costs and increasing sales, which is reflected in the value of the company.Companies focus on maintaining a variable level of liquidity that suitsThe company's need from time to time, while maintaining the minimum level all the time, in order to protect the company from potential risks and thus increase the value of the company.
Keywords: predictive analytics; future stock prices; listed companies in the market